The self-assessment of hospitality employment skills among vocational students in Malaysia / Nor Aziah Ahmad - Nor Aziah , Ahmad (2018)
Malaysia needs high skilled workforce to support growth of the industry. With dynamically changing job market and progressive technological change, employees are expected to keep abreast of global economics. In the process of achieving the status of developed nation by the year 2020, Malaysia needs to restructure its workforce to ensure that middle level workers are highly skilled. Current job environment demands multi-task and skills. Thus, university graduates must be prepared to meet the demand especially in the hospitality industry. The purpose of this study is to identify the hospitality employability skills consist of fifteen elements of employability skills among vocational students in Malaysia. The objective of this study is to identify the level of hospitality employability skills among vocational students. This study also analyzed whether there are significant differences in the competency level of vocational students by gender. The research also identifies the differences of hospitality employability skills by location (rural and urban), examines the determinants of hospitality employability skills among bakery and culinary students separately, identifies differences between perceived importance and competency gained in employability skills among bakery and culinary students and examines the skills that are needed by students for entering the hospitality profession. This research applied quantitative and qualitative methodology. The respondents consist of final year students in bakery and culinary programme. Stratified sampling was used to select students in hospitality programs from 22 vocational colleges in Malaysia. Questionnaires were distributed to eight hundred forty one students in five regions in Malaysia. Interview was also conducted with ten vocational students in central region, Malaysia. Descriptive and inferential statistics such as T- test and multiple regression analysis were used to analyse the quantitative data. The results showed that the level of hospitality employability skills among vocational students in Malaysia were at high level of competent and importance (93.2%). Findings also revealed that male students are more competent in hospitality employability skills compared to female students in vocational colleges. The result also provided evidence that rural students are more competent in hospitality employability skills compared to urban students in vocational colleges. The result found that the competence gained by bakery students in terms of employability skills is lower than the importance perceived by those students. The findings also showed that the competence gained by culinary students in terms of employability skills is lower than the importance perceived by those students.